Evaluation of vermicompost and chemical fertilizers on performance of Pak choi (Brassica rapa cv. Hong Tae) and soil biological process - Tripathi, K. M.; Dhakal, D. D.; Sah, S. C.; Baral, D. R.; Sharma, M. D. (Journal of the Institute of Agriculture and Animal Science, 2018)
A field experiment was conducted to evaluate the effect of vermicompost and chemical fertilizers on the performance of Pak choi (Brassica rapa CV. Hong Tae) in Chitwan Nepal during November 2012 to January 2013. Four levels of vermicompost (0, 5, 10 and 15 t/ha) and four levels of NPK equivalent in the form of inorganic fertilizer (100, 50, 25 and 0% of recommended doses of 100:60:60 Kg/ha) in 16 combinations were assessed for yield, yield contributing parameters of Pak choi and microbial activities of soil. All levels of chemical fertilizers increased plant height, leaf number and chlorophyll content of leaves but they had no effect in increasing root length. Chemical fertilizers at 100:60:60 kg NPK/ha increased biological and economic yield of Pak choi. However, all levels of chemical fertilizers were found strongly suppressing in soil microbial activities. Vermicompost on the other hand increased root length, leaf number, biological and economic yield and more significantly increased soil microbial activities resulting in increased level of soil respiration. Chemical fertilizers were effective in increasing plant growth but suppressed microbial activities of soil. Vermicompost on the other hand was effective in long run through slow release of plant nutrients and improving soil health by increased soil microbial activities. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 243-250